QUICK RESPONSE CODE (QR Code)-ASSISTED INTERACTIVE MEDIA ON VIRUS FOR HIGH SCHOOL STUDENT - Mawaddah, Kuni; Zulfia, Firda Ama; Yunanda, Intan (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green Technology, 2017)
One of the technological innovations in education is the creation of interactive learning media. QR Code technology can be used to connect between various media. This study aims to develop QR Code-assisted interactive media on virus for high school student. To learn virus as a microscopic, require various media that can visualize well as interactive media that integrated various other media such as media images and video. The integration of various media can be done with the help of QR Code technology. This research method is a 4D development model adapted from Thiagarajan. In this study, we only do research until the design phase because of limited funds and time. The results of research in the form of interactive media product with QR Code assisted with basic competence in SMA X class that is 3.4 analyze the structure, replication and role of virus in life.